Saccharide-mediated antagonistic effects of bark beetle fungal associates on larvae - Wang, Bo (The Royal Society, 2013)
Bark beetles are among the most destructive of pine forest pests and they form close symbiotic relationships with ophiostomatoid fungi. Although some fungi are considered to be mutualistic symbionts of bark beetles with respect to the supply of nutrients, detrimental effects of fungal symbionts on larval growth have also been frequently reported. The mechanisms of such antagonistic effects are hypothesized to be a decrease in nutritional resources caused by competition for saccharides by the fungi. Here, we provide experimental evidence that three beetle-associated fungi modify the nutritional content of an artificial phloem diet, leading to a detrimental effect on the growth of Dendroctonus valens larvae. When larvae were fed a diet of pine phloem in agar medium colonized with any of these fungi, feeding activity was not affected but weight significantly decreased. Additional analysis showed that fungi depleted the fructose and glucose concentrations in the phloem media. Furthermore, these detrimental effects were neutralized by supplementing the media with fructose or glucose, suggesting that fungi may affect larval growth by modifying diet saccharide contents. These data indicate that fungus-induced nutritional changes in bark beetle diet can affect larval growth, and that the mechanism involves fungus-induced saccharide depletion from the larval diet.